Making strategy work - RAIMOND, P. (1990)
Presents guidelines as to how to organise the planning process with the use of an external facilitator, including the development of trust, recourse to weekend 'retreats', the requirement to create a plan which is believed can be successfully implemented and to convene regular progress meetings.